Aprendizagem significativa de grandezas e medidas: aspectos da diferenciação progressiva e da reconciliação integrativa na ZDP - Elias, Sabrina (2024)
This research is theoretically based on Ausubel's Theory of Meaningful Learning, which has the principle of considering, in the teaching and learning process, the prior knowledge that the student already has in their cognitive structure. The process of new learning must be non-literal and non-arbitrary. Associated with it, we will also use the Sociointeractionist Theory proposed by Vygotsky, in which social interaction in the classroom is fundamental and the teacher has the role of mediator. We will also use the History of Science as a pillar, as it allows the student to have a more concrete view of the real nature of science, its methods and limitations, in addition to what can motivate the student to meaningful learning. The main objective of this research is to understand how the process of meaningful learning of quantities and measurements occurs through an investigative teaching sequence based on the History of Science, for students in the 1st year of High School. We carried out the research at a state school in Júlio de Castilhos called E.E.E.M. Dr. Júlio Prates de Castilhos, which has a varied audience of students from the center and interior of the city. The teaching methodology used was based on investigative teaching sequences where activities are planned from the point of view of the material and didactic interactions. This research is characterized as qualitative, since it will consider the study of lived experience and the processes of social interaction in its development. Data production was carried out using a survey test, logbooks, student records, audio recordings and photographs. The analysis was carried out according to Bardin's Content Analysis, in the probing test and an interpretative (explanatory) analysis in the other data. This research is characterized as participatory research since the researcher is part of the data production. The process of progressive differentiation and integrative reconciliation, essential for meaningful learning, was evident, and that these occurred in the Zone of Proximal Development. The evidence that led to these conclusions comes from the analysis of the evolution of concepts and the relationship between them, presented by the students. It is hoped that the results of this research can help teachers of basic education in physics, mathematics and science in their choice of methodology, being aware of how this significant learning process takes place.